Combined effects of ammonia nitrogen, nitrite, salinity, and temperature negatively impact the growth, survival, physiological, and biochemical parameters, and hepatopancreatic structure of Litopenaeus vannamei - Xuenan Li; Linwei Wang; Xilin Dai (Aquaculture, 2025)

The Distribution Characteristics and Influencing Factors of the CO2 Fluxes Across the Sea–Air Interface in the Artificial Reefs Area of Sanheng Island - Mingdong Zhu; Kai Wang; Xu Zhao; Linwei Dai; Lei Chen; Hanyu Zhou (Journal of Marine Science and Engineering, 2024)
In order to study the impact of artificial reef construction on marine carbon sinks, a one-year monitoring and analysis were carried out in the Sanheng artificial reef areas of Shengsi Island. The main parameters observed were sea surface temperature, salinity, pH, total alkalinity (TA), and dissolved inorganic carbon (DIC). The partial pressure of CO2 (pCO2w) in the surface water and the CO2 flux (FCO2) across the sea–air interface were calculated and analyzed. The results showed that the annual range of surface water pCO2w was 34.48~501.53 μatm, and the partial pressure of CO2 decreases in the following order: winter, spring, autumn, summer. The FCO2 was significantly negatively correlated with temperature and significantly positively correlated with salinity and TA. The FCO2 in the four seasons decreases in the following order: winter, spring, autumn, summer. The annual sea–air flux in the survey area ranged from −108.79 to 41.74 mmol m−2 d−1. In winter, both the reef area and the control area displayed positive FCO2 values, indicating a source of CO2, while in the other three seasons, CO2 flux values were negative, indicating an overall CO2 sink. Additionally, in autumn, the reef area exhibited a stronger CO2 sink than the control area. The results indicated that the construction of artificial reefs has a certain carbon sink effect, with no significant difference in effectiveness between different artificial reef construction models.

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

Effects of acid mine drainage on photochemical and biological degradation of dissolved organic matter in karst river water - Linwei Li; Xingxing Cao; Chujie Bu; Pan Wu; Biao Tian; Yongheng Dai; Yeye Ren (Journal of Environmental Sciences, 2024)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Seasonal variations of monocarbonyl and dicarbonyl in urban and sub-urban sites of Xi’an, China - K. F. Ho; Steven Sai Hang Ho; W. T. Dai; J. J. Cao; Ru-Jin Huang; Linwei Tian; W. J. Deng (Environmental Monitoring and Assessment, 2014)